Cutaneous wound healing in castrated and uncastrated rabbits: Comparative study - Hameed, Falah Mahmood (Journal of Kerbala for Agricultural Sciences, 2024)
The purpose of this research is to examine the effects of testosterone on rabbits' full-thickness skin wounds. A full-thickness (2 cm2) wound was produced in the dorsal back region of sixteen (16) mature male rabbits that were in good clinical condition and weighed between (1.3 and 1.8 kg). Administration intramuscularly of a mixture of 5mg/kg of xylazine hydrochloride 35mg/kg of ketamine hydrochloride, and 1 mg/kg of Diazepam. At 3, 7, 14, and 21 days after the formation and treatment of the wound, each group was divided into 4 subgroups (two wounds/subgroup) for the purpose of clinical evaluation. The wound healing rate was monitored for 21 days. The level of serum testosterone in both groups was also examined at the same time. The results revealed, clinically, that the rate of skin healing in castrated rabbits was quicker than in non-castrated rabbits. In addition, the results revealed that castrated groups have enhanced cellularity and increased vasculature, which is superior to those in non-castrated groups. Conclusion: The clinical findings confirmed the effects of testosterone on cutaneous wound healing.